2011
DOI: 10.1590/s0100-06832011000600001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da aptidão agrícola de solos do Acre por diferentes especialistas

Abstract: Os sistemas de avaliação da aptidão ou do potencial agrícola das terras têm sido utilizados nas diversas regiões do Brasil, por várias equipes e com múltiplas aplicações. O objetivo deste trabalho foi avaliar, para solos no Estado do Acre, como diferentes especialistas percebem a importância relativa dos indicadores de um sistema de aptidão agrícola e como eles interpretam esses atributos para a definição das diferentes classes de aptidão. Foram utilizados 10 perfis de solos analisados para a IX Reunião Brasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
3
0
6
Order By: Relevance
“…Bie & Beckett (1973) compared soil maps drawn independently by different pedologists of a same area and observed considerable differences in the resulting maps. In a similar study analyzing land suitability maps, Delarmelinda et al (2011) concluded that the evaluation was contrasting even based on the same soil profiles and environments. Also, Focht (1998) reported the influence of the scientist on the classification of land use suitability in the same watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Bie & Beckett (1973) compared soil maps drawn independently by different pedologists of a same area and observed considerable differences in the resulting maps. In a similar study analyzing land suitability maps, Delarmelinda et al (2011) concluded that the evaluation was contrasting even based on the same soil profiles and environments. Also, Focht (1998) reported the influence of the scientist on the classification of land use suitability in the same watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Caracteriza-se pela aplicação intensiva de capital e de resultados de pesquisa para manejo, melhoramento e conservação das condições das terras e lavouras. A motomecanização está presente nas diversas fases da operação agrícola (RAMALHO FILHO;BEEK, 1995;DELARMELINDA, 2011;2014;WADT, 2013).…”
Section: Resultsunclassified
“…Dessa forma, variações de interpretação podem resultar na dificuldade da aplicação de métodos, pois causam incertezas, especialmente, quando são inseridas nos sistemas de informação geográficas (DELARMELINDA et al 2011).…”
Section: Introductionunclassified